(untitled) (Journal of Plant Disease Sciences, 2020)
Chickpea ( ) is grown extensively in India as an important legume crop. Seed borne fungi affect chickpea crop leading to cause major loss in quality and quantity of the seed. Thus’ in present study the seedborne mycoflora associated with chickpea crop were detected and isolated. During the present investigation seed samples of Chickpea variety, JAKI-9218 were tested for the detection and identification of seed borne mycoflora by various methods , standard blotter